PENERAPAN TEOLOGI AL-MAUN DI PENDIDIKAN BELA DIRI: STUDI KASUS DI TAPAK SUCI UHAMKA - Robbani, Hamdan Thufail (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research will examine how the relevance of Al-Maun theology developed by Muhammadiyah on educational practices in UKM tapak suci UHAMKA which carries on the principles of progresive and moderation. In addition, this research also examines how UKM tapak suci UHAMKA actualises and externalises the principles of tawhidaan and social care in the community as an autonomous organisation owned by Muhammadiyah. This research will use qualitative methods with a document review approach and case studies in collecting relevant data. The results obtained from this research are that UKM Tapak Suci UHAMKA has mobilised various kinds of abilities to contribute to the issues emphasised by the Muhammadiyah association. As well as issues of social divinity and social care which are the fundamental foundations of the Muhammadiyah organisation. Keywords: Al-Maun Theology; Moderation; Progresive; Tapak Suci.